2005
DOI: 10.1002/jmv.20513
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of functional B cell memory against parvovirus B19 capsid proteins may be associated with resolution of persistent infection

Abstract: Parvovirus B19 (B19) infection can occur during acute lymphoblastic leukemia and persistent viral infection can occur despite intravenous immunoglobulin administration. Here, evidence is presented that resolution of persistent B19 infection in an acute lymphoblastic leukemia patient may be associated with the simultaneous strengthening of antigen-specific B cell memory against the B19 capsid protein VP2 and diminution in the memory response against the B19 non-structural protein 1 (NS1). Determination of antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
4
0
1
Order By: Relevance
“…Recently, Corcoran et al. [203] showed persistent infection in a child with acute lymphatic leukaemia despite the treatment with intravenous immunoglobulin. Interestingly, resolution of the infection was associated with the simultaneous strengthening of antigen‐specific B‐cell memory against B19 VP2 and diminution in the memory response against B19 NS1.…”
Section: Immune Responses In B19 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Corcoran et al. [203] showed persistent infection in a child with acute lymphatic leukaemia despite the treatment with intravenous immunoglobulin. Interestingly, resolution of the infection was associated with the simultaneous strengthening of antigen‐specific B‐cell memory against B19 VP2 and diminution in the memory response against B19 NS1.…”
Section: Immune Responses In B19 Infectionmentioning
confidence: 99%
“…The situation in persistent B19 infection may thus resemble that of HBV infection, and the increased T-cell activity seen after interferon treatment of HBV infection, suggests that a similar approach might prove beneficial also in B19-persistent infection [202]. Recently, Corcoran et al [203] showed persistent infection in a child with acute lymphatic leukaemia despite the treatment with intravenous immunoglobulin. Interestingly, resolution of the infection was associated with the simultaneous strengthening of antigenspecific B-cell memory against B19 VP2 and diminution in the memory response against B19 NS1.…”
Section: Immune Responses In Persistently Infected Individualsmentioning
confidence: 99%
“…Assays based on exploitation of the P antigen receptor of B19, known as receptor-mediated hemagglutination (RHA), have been proposed as a cheap way of screening plasma and apparently detect whole virus, however the assay sensitivity is low when compared to PCR and, more importantly, it has not been assessed in an obstetrics context (Cohen and Bates, 1995;Sato et al, 1995;Wakamatsu et al, 1999). In cases where patients are treated with intravenous immunoglobulin (IVIG) to treat chronic B19 infection, assessment of antigen-specific B cell memory allows one to discriminate IVIG-and individual-derived B19 IgG, which is important in determining the seroconversion status of the individual (Corcoran et al, 2005a).…”
Section: Alternative Detection Methodsmentioning
confidence: 99%
“…Further analyses identified two discrete A + T rich elements within the V1 S107 variable heavy chain promoter were bound by a protein complex later identified to contain Bright (3). Intriguingly, further analyses showed potential Bright-binding motifs in about half of the murine V H promoters, and binding sites were not restricted to specific V region families (30, 31). Similarly, only a subset of human V H promoters had binding sites for Bright (32).…”
Section: Gene Targets For Brightmentioning
confidence: 95%